REPRESENTATION OF CONSUMMATE LOVE THROUGH CHARACTERS OF JOSEE AND TSUNEO IN JOSEE THE TIGER AND THE FISH (2020) BY SEIKO TANABE - Febriani, Feeni; Dinanti, Putri Ayienda (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Love is something that humans constantly seek to understand and express, and it frequently appears in various media narratives. Based on this idea, this study explores how a particular type of love is portrayed in the Japanese animated film Josee, the Tiger and the Fish (2020). This research adopts a qualitative approach and applies Robert Sternberg’s Triangular Theory of Love to examine the relationship between the two main characters. The research process involves several stages: collecting data in the form of images and dialogues from selected scenes, categorizing the data into themes based on Sternberg’s three components of love (intimacy, passion, and commitment), conducting thematic analysis to identify patterns in the representation of love, and drawing conclusions on how the characters’ self-image is shaped through expressions of love in the film. The findings reveal that the relationship between Josee and Tsuneo exemplifies what Sternberg defines as consummate love—a complete form of love that includes emotional closeness, physical affection, and long-term commitment. Their bond is illustrated through honest communication and a supportive relationship, while passion and commitment are portrayed in a balanced way. This film demonstrates that animation can serve as an effective medium for representing deep and meaningful aspects of human relationships, offering a richer understanding of the essence of love. ABSTRAK Cinta adalah sesuatu yang selalu ingin dipahami dan diungkapkan manusia, dan hal tersebut kerap muncul dalam berbagai narasi media. Berdasarkan gagasan tersebut, studi ini mengkaji bagaimana jenis cinta tertentu ditampilkan dalam film animasi Jepang Josee, the Tiger and the Fish (2020). Penelitian ini menggunakan pendekatan kualitatif dengan memanfaatkan teori Segitiga Cinta dari Robert Sternberg untuk mengeksplorasi hubungan antara dua tokoh utama. Penelitian dilakukan melalui beberapa tahapan, yaitu pengumpulan data berupa gambar dan dialog dari adegan terpilih, pengelompokan data ke dalam tema-tema sesuai indikator teori (keintiman, gairah, dan komitmen), analisis tematik untuk mengidentifikasi pola representasi cinta, serta penarikan kesimpulan mengenai bagaimana pencitraan diri tokoh dibentuk melalui ekspresi cinta dalam film. Hasil penelitian menunjukkan bahwa hubungan antara Josee dan Tsuneo mencerminkan bentuk cinta sejati sebagaimana dijelaskan oleh Sternberg—cinta yang mencakup keintiman emosional, gairah fisik, dan komitmen jangka panjang. Kedekatan mereka tergambar melalui percakapan yang jujur dan hubungan yang suportif, sementara gairah dan komitmen hadir secara seimbang dalam interaksi mereka. Film ini menunjukkan bahwa animasi dapat menjadi medium yang efektif untuk merepresentasikan dinamika cinta yang utuh dan bermakna, serta memberikan pemahaman lebih dalam tentang esensi cinta dalam hubungan manusia.